Satisfaction of users with assistive technology service delivery: An exploratory analysis of experiences of parents of children with physical and multiple disabilities. (3rd July 2016) - Desideri, Lorenzo; Stefanelli, Brunella; Bitelli, Claudio; Roentgen, Uta; Gelderblom, Gert-Jan; de Witte, Luc
Abstract: Objective : To describe experience of assistive technology service delivery (ATSD) by parents of children with physical or multiple disabilities (aged 3–18 years). Method : Forty-seven of 115 parents participated in a postal survey assessing satisfaction with the ATSD process, employing the QUEST 2.0 and the KWAZO scales. Six of these participated in two focus groups. Descriptive statistics were used for satisfaction scores. The focus group transcripts were coded and combined with survey results by two independent researchers. Results : Low satisfaction scores were reported for follow-up, AT delivery, maintenance services, access to services, coordination, and efficiency of ATSD. Several barriers to and facilitators of ATSD were mentioned and solutions to improve ATSD quality were identified. Conclusion : Evaluation of parents' service experience is central for identifying shortcomings in ATSD. Health professionals are advised to utilize validated instruments and strategies to assess effectiveness of technological interventions and to assure ATSD quality.